"There's a Bit of a Ripple-effect": A Social Identity Perspective on the Role of Third-Places and Aging in Place. Issue 5 (June 2021) - Fong, Polly; Haslam, Catherine; Cruwys, Tegan; Haslam, S. Alexander
Urban sociology highlights an important role that a city's social infrastructure, or "third-places, " play in supporting healthy communities. Informed by social identity theorizing, this study explores when and why older adults engage with third-places and how a sense of wellbeing can be derived from their participation. Focus-group interviews were conducted with a sample of community-dwelling older adults ( N = 31) to examine the nature of one such third-place, a suburban neighborhood bridge club. Thematic analysis suggests that (a) the socio-spatial context of third-places can both enable and restrict participation, (b) third-places can support positive social identities (as bridge players, club members, locals), (c) enacting these identities in third-places facilitates a sense of wellbeing, and (d) third-places are potential connectors to the wider community. We discuss the policy implications for the development of age-friendly cities and the role of social identity processes in engaging with community groups in third-places.